Short-Term Effect of Biochar on Soil Organic Carbon Improvement and Nitrous Oxide Emission Reduction According to Different Soil Characteristics in Agricultural Land: A Laboratory Experiment - Jong-Mun Lee; Do-Gyun Park; Seong-Su Kang; Eun-Jung Choi; Hyo-Suk Gwon; Hyoung-Seok Lee; Sun-Il Lee (Agronomy, 2022)
Biochar application has been considered as a promising solution to address the effects of modern agriculture on climate change. However, there is a lack of research on the biochar application of greenhouse gas emissions based on poor soils in Korean agricultural land. Therefore, this study aimed to evaluate the effects of biochar application according to different soil characteristics on soil organic carbon (SOC) improvement and greenhouse gas reduction. The incubation experiments were conducted for 49 days and used different feedstock (barley straw and poultry manure) and biochar application rates (0, 5, 10, and 20-ton ha−1) in four soil characteristics (upland, U; greenhouse, G; converted land, C; reclaimed land, R). The results of this study showed that the SOC increased significantly in all soils after biochar application. The increasing SOC rate was the highest in poor soil. Biochar 20-ton ha−1 treatment significantly reduced N2O emissions by 33.2% compared with the control. Barley straw biochar significantly reduced N2O emissions from all soils. Barley straw biochar decreased approximately 74.5% of N2O emissions compared with poultry manure biochar. Poultry manure biochar improved SOC and reduced N2O emissions in poor soil. However, in poultry manure biochar treatment in U and G soil, N2O emissions increased. In conclusion, barley straw biochar application was found to suppress N2O emissions and improve the SOC in all soil characteristics of agricultural land. In addition, the soil carbon storage effect and N2O reduction effect of biochar were the highest in poor soil. Thus, the biochar application can be a potential agricultural practice for improving soil quality and decreasing N2O emissions in domestic agricultural soil.